2021
DOI: 10.1007/s00590-021-03024-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in patients undergoing elective primary lower limb arthroplasty

Abstract: Purpose Recent research has outlined the increasing incidence of acute kidney injury (AKI) and its effect on morbidity/mortality. There is evidence that current rates are significantly under-reported nationally, with uncertainty about pre-operative factors that might influence AKI reduction and the impact on other healthcare outcomes such as mortality and later Chronic Kidney Disease (CKD) development. We set out to help address these current deficiencies in the literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
1
4
0
4
Order By: Relevance
“…Our results regarding the number of risk factor drug classes prescribed concur with those of Bell et al , perhaps supporting our suggestion of a synergistic impact of these drugs on renal blood flow resulting in an increased risk of AKI 6. Our findings support those previously made with regard to the effect of postoperative AKI on length of hospital stay and postoperative mortality 1 3–5…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results regarding the number of risk factor drug classes prescribed concur with those of Bell et al , perhaps supporting our suggestion of a synergistic impact of these drugs on renal blood flow resulting in an increased risk of AKI 6. Our findings support those previously made with regard to the effect of postoperative AKI on length of hospital stay and postoperative mortality 1 3–5…”
Section: Discussionsupporting
confidence: 92%
“… 1–5 A large-scale cohort study estimated the incidence of AKI for postoperative T&O patients at 10.8%. 6 Studies focusing on AKI following elective procedures found rates of 6.8% 5 and 8.2% 1 compared with 17% of patients following emergency surgery. 3 7 Importantly, while undergoing an operation is in itself a risk factor for developing an AKI, emergency T&O patients in particular are often at greater risk, given their frailty and comorbidities.…”
Section: Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, recent studies have shown an increase in the incidence of AKI and its impact on morbidity and mortality. 1,9,15,16 However, although potential risk factors for AKI have been examined in studies of orthopedic patients, only limited evidence is available to guide targeted intervention strategies aimed at reducing the risk of AKI. 15,17,18 Few studies have investigated AKI after spinal surgery, especially surgery for degenerative spinal disease.…”
Section: Introductionmentioning
confidence: 99%
“…1,9,15,16 However, although potential risk factors for AKI have been examined in studies of orthopedic patients, only limited evidence is available to guide targeted intervention strategies aimed at reducing the risk of AKI. 15,17,18 Few studies have investigated AKI after spinal surgery, especially surgery for degenerative spinal disease. The true incidence and predictors for AKI following degenerative spine surgery have yet to be evaluated.…”
Section: Introductionmentioning
confidence: 99%